The Tremendous Oath: Cosmological Horizons and the Hermeneutics of Stellar Positions (Sūrat Al-Wāqiʿah 56:75–76) - Umar Iqbal Butt (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2026)
The Qurʾān frequently employs oaths involving celestial phenomena to underscore the veracity of Revelation. However, the oath found in the closing passages of Sūrat al-Wāqiʿah (56:75–76) distinguishes itself through unique syntactic negation and a specific focus on the "falling places" (mawāqiʿ) of stars rather than the celestial bodies themselves. This paper provides a multidisciplinary examination of this oath, synthesizing classical philology (fiqh al-lughah), the history of Islamic astronomy, and contemporary astrophysics. By analyzing the lexical range of the root w-q-ʿ alongside physical phenomena such as light-time delay, gravitational lensing, and stellar collapse, this study argues that the Qurʾānic phrasing anticipates a distinction between perceived observation and physical reality. The paper concludes that the "tremendousness" (ʿaẓamah) of the oath serves as an epistemological bridge, challenging human perception to validate the unseen source of the Qurʾān through the visible, yet deceptive, order of the cosmos.